Water decoction of Pericarpium citri reticulatae and Amomi fructus ameliorates alcohol-induced liver disease involved in the modulation of gut microbiota and TLR4/NF-κB pathway - Zhang, Xing-Min; Huang, Yue-Chang; Chen, Bai-Zhong; Li, Qian; Wu, Pan-Pan; Chen, Wen-Hua; Wu, Ri-Hui; Li, Chen (Frontiers in Pharmacology, 2024)
Introdution: Alcohol consumption alters the diversity and metabolic activity of gut microbiota, leading to intestinal barrier dysfunction and contributing to the development of alcohol liver disease (ALD), which is the most prevalent cause of advanced liver disease. In this study, we investigated the protective effect and mechanism of aqueous extraction of Pericarpium citri reticulatae and Amomi fructus (PFE) on alcoholic liver injury.: C57BL/6 mice were used to establish the mouse model of alcoholic liver injury and orally administered with 500 and 1000 mg/kg/d of PFE for two weeks. Histopathology, immunohistochemistry, immunofluorescence, western blot, qRT-PCR and 16S rDNA amplicon sequencing were used to analyze the mechanism of action of PFE in the treatment of alcohol-induced liver injury. Results: Treatment with PFE significantly improved liver injury induced by alcohol, as illustrated by the normalization of serum levels of alanine aminotransferase, aspartate aminotransferase, total triglycerides and cholesterol in ALD mice in a dose dependent manner. Administration of PFE not only prominently maintained intestinal barrier integrity by upregulating mucous production and tight junction protein expressions, but also sensibly reversed the dysregulation of intestinal microecology in alcohol-treated mice. Furthermore, PFE treatment significantly reduced hepatic lipopolysaccharide (LPS) and attenuated oxidative stress and inflammation related to the TLR4/NF-κB signaling pathway. Additionally, PFE supplementation significantly promoted the production of short-chain fatty acids (SCFAs) in ALD mice. Conclusions: Administration of PFE effectively prevented alcoholic-induced liver injury may be related to the regulation of LPS-involved gut-liver axis, which providing valuable insights for the development of drugs for the prevention and treatment of ALD.